Train Accident In Bangladesh: Causes And Remedies (Bangladesh Journal of Public Administration, 2021)
The success of a public transport organisation like the railway depends largely upon the standard of safety and efficiency of the service rendered by it. The lack of public faith in its ability to operate without endangering the life and property of the users may underlnine the financial viability of the organisation. There is no accident-free transport system. However, an accident has more consequences for the railway system than for other modes of transport. This is because railway accidents have a two-fold effect, namely, loss of life and property and an adverse effect on traffic lnobility as it takes time to clear the railway track and malce it fit for further train movement.